Interactive marketing: Revolution or rhetoric? - Miles, Chris J. (Taylor and Francis, 2010)
This book critically examines the rhetoric surrounding current trends in the adoption of tropes of interactivity in marketing communication. Concepts such as viral advertising, customer-generated content, brand communities and the whole panoply of Web 2.0-mediated marketing technologies all have their foundations in an overt positioning of interactivity as the savior of effective marketing communication. Yet, what exactly is meant by interactivity in these contexts and how far does it represent a revolution in the methodologies of marketing? Anchoring his analysis in a critique of the assumptions of control embedded in current marketing communication models and the rhetorical analysis of exemplar texts from the Marketing Management, Customer Relationship Management, Viral Marketing and Buzz Marketing paradigms, Chris Miles investigates the constructions and reconstructions of discourse that surround the uses of interactivity in contemporary marketing discourses. In doing so, he offers a radical new model of marketing based upon a recursive, constructivist understanding of communication that uses metaphors of invitation and exploration to rebuild interactivity at the center of marketing. The work culminates in a reading of the theory of Relationship Marketing that uses autism as an allegory to interrogate the communicative paradox at the heart of this contemporary marketing panacea. © 2010 Taylor & Francis.